IMPROVING GROWTH PERFORMANCE OF YANKASA RAMS FED CHEMICAL-TREATED GROUNDNUT SHELLS SUPPLEMENTED WITH EXOGENOUS ENZYMES - MILLAM, Jacob Jafiya; Abdu, Salisu Bakura; Yashim, Suleiman Makama; Adamu, Hanwa Yusuf (FUDMA Journal of Sciences, 2022)
This study evaluated the effect of chemical treated groundnut shells supplemented with xylanase and glucanase in rations of Yankasa rams on growth performance in Nigeria. It was carried out at the Small Ruminant Unit of Adamawa Sta e University Teaching and Research Farm, Mubi. The study was designed in a 4Ã—2 factorial arrangement with 4 rams per treatment in a completely randomised design. The experimental animals were housed in well ventilated environment and they were comfortable. Basic routine management were carried out. The experimental rations were formulated to meet the requirements of the rams. The experiment lasted for 90 days. Parameters under consideration were weight gain, feed intake and feed conversion ratio. Significant (P<0.05) and non-significant (P>0.05) effects were observed from the results obtained. The results show that rams receiving glucanase and untreated groundnut shells improved both weight gain (8.71 kg) and average daily weight gain (103.64 g/d); and increased both feed intake (65.79 kg) and average daily feed intake (783.20 g/d). However, feed conversion ratio was relatively least in the group of rams receiving urea treated groundnut shells (7.18) compared to other treatments. It was concluded that untreated and urea treated groundnut shells supplemented with glucanase could improve weight gain, feed intake and feed efficiency in Yankasa rams.